Polymer - dendron based micelles as drug delivery systems - Bilgen, Nuray. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
Polymeric micelles are remarkable nominees for drug delivery systems due to their excellent biocompatibility also they provide high loading capacity to hydrophobic inner core and increase drug solubility. In water, micelles can be formed via self-assembly and this micelle formation is connected to the solubility difference of the hydrophilic and hydrophobic part. Hydrophobic parts form the inner core of the micelle and hydrophilic part which surrounds the core form the sphere of micelle. In our study, polymer-dendron conjugates are prepared via Huisgen type „click‟ reaction using polyester dendrons and PEG. Biocompatible PEG is used as the polymer to provide water solubility to hydrophobic drug molecules. The conjugation of Dendron to PEG followed by functionalization of the dendron periphery with hydrophobic moiety. This system provided the hydrophilic-hydrophobic balance necessary to form the polymeric micelles in aqueous media. Dendron surface was further decorated with drug molecules to yield the micellar drug delivery system.
Keywords: Surface acting agents.; Micelles.; Neutrons -- Scattering.